Numerical simulation through experimental validation of latent and sensible concrete thermal energy storage system. (July 2022) - Martelletto, Francesca; Doretti, Luca; Mancin, Simone
Abstract: A new type of concrete with PCM (Phase Change Material) thermal energy storage system is presented. The system, developed for industrial applications, is supposed to operate with a temperature up to 400 °C and the PCM added mixture presents enhanced thermal performances. A binary mixture of salts was used as PCMs, composed of 40% of KNO3 and 60% of NaNO3, and they were absorbed by diatomite, a porous fossil flour. A stainless-steel pipe is inserted in the centre of a concrete cylinder, the whole system is insulated. The experimental tests studied two concrete mixtures, with 5% PCM in weight and without it. The charging stage is carried out via Joule's effect and the module is then cooled with compressed air through the pipe. The two mixtures were tested under the same operating conditions. The module was numerically simulated and the results were compared with previous experimental tests to calibrate the model. Further numerical simulations were conducted to test other PCM percentages, under the same conditions as the experimental tests and with thermal oil as heat transfer fluid, to evaluate a possible working scenario. The results showed that the PCM integration into the storage system led to an impressive improvement in thermal performance. The amount of stored and released thermal energy increased with the PCM integration, coming to double its original value with the highest PCM percentage integration simulated, which corresponds to 40%. Highlights: Thermal storage concrete with PCM module is numerically investigated and compared to experimental data. The validated model was used to run different simulations and explore a real scenario for industrial applications. The exchanged thermal energy is assessed in the charging and discharging phase, considering different PCM percentages. The results showed an improvement in the thermal performances of the module with the integration of PCM.